The effectiveness of protected areas in the context of decentralization. (June 2021) - Miteva, Daniela A.; Pattanayak, Subhrendu K.
Highlights: Decentralization proxied by direct elections, district splitting, and district head changes increased deforestation. Decentralization discouraged the use of fires. Decentralization through changes in the threat to forests, enforcement, and accountability impacted protected areas. Direct elections improved protected area performance, while district splitting and district head changes weakened it. Abstract: While protected areas (PA) remain a key conservation strategy globally, their performance is likely shaped by the socio-political context in which they exist. Although decentralization is a good example of such a contextual phenomenon in multiple locations globally, it is rare to find quantitative empirical analyses of how it moderates PA effectiveness. We evaluate how the decentralization in Indonesia (proxied by the introduction of direct elections, district head ( bupati ) change, and district splitting) influenced PA effectiveness between 2000 and 2008. Focusing on three outcomes - deforestation, forest fragmentation, and fires, we apply a quasi-experimental approach to a carefully constructed spatially explicit village-level panel dataset, combined with geospatial biophysical and physio-geographic data. We hypothesize that the moderating influence of decentralization on PA effectiveness depends on whether decentralization increased threats to forests, strengthened local accountability, or weakened enforcement. On average, we find direct elections improved the PA impact in terms of reducing deforestation in protected villages, but had no statistically significant effect on forest fragmentation, fires, or leakage. On average, we find district splitting increased forest fragmentation in the recently protected villages, but had no statistically significant impact on deforestation and fires. On average, we find the bupati change had no statistically discernible influence on PA impacts on deforestation, fragmentation or fires. Given the increasing threats to forests due to decentralization, these results imply that district splitting and the bupati change weakened enforcement inside PAs with regards to deforestation and forest fragmentation, in contrast to direct elections. By highlighting the potential channels through which decentralization in Indonesia impacted forests, we offer insights into the effectiveness of a common conservation policy in the country. Broadly, we contribute to the conservation impact evaluation literature by quantitatively examining how political economy influences the performance of conservation policies.